2017
DOI: 10.1289/ehp300
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Exposure to Urban Air Pollution and Influences on Placental Vascularization Indexes

Abstract: Background:It has been widely demonstrated that air pollution can affect human health and that certain pollutant gases lead to adverse obstetric outcomes, such as preeclampsia and fetal growth restriction.Objectives:We evaluated the influence of individual maternal exposure to air pollution on placental volume and vascularization evaluated in the first trimester of pregnancy.Methods:This was a cross-sectional study on low-risk pregnant women living in São Paulo, Brazil. The women carried passive personal NO2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 58 publications
0
29
0
3
Order By: Relevance
“…Impairing placental function and decreasing transplacental oxygen and nutrient transport could be among potential mechanisms by which air pollution could affect foetal brain development during pregnancy. Evidence from birth cohorts suggests that air pollution affects placental function measured by Doppler ultrasound (negative effects on umbilical artery resistance in one study, but not in another during the second and third trimester; and negative associations on flow indices in the first trimester). There is consistent evidence that impaired placental function disrupts foetal neurodevelopment in animals and neurobehavioural development in children.…”
Section: What Are the Potential Mechanisms Underlying The Effects Of mentioning
confidence: 88%
See 2 more Smart Citations
“…Impairing placental function and decreasing transplacental oxygen and nutrient transport could be among potential mechanisms by which air pollution could affect foetal brain development during pregnancy. Evidence from birth cohorts suggests that air pollution affects placental function measured by Doppler ultrasound (negative effects on umbilical artery resistance in one study, but not in another during the second and third trimester; and negative associations on flow indices in the first trimester). There is consistent evidence that impaired placental function disrupts foetal neurodevelopment in animals and neurobehavioural development in children.…”
Section: What Are the Potential Mechanisms Underlying The Effects Of mentioning
confidence: 88%
“…In this context, it is important to highlight that foetus has higher exposure than mothers in relation to their body size. Moreover, foetal life exposure results in maternal effects such as plasma viscosity, or systemic low‐grade inflammation, hormonal disruption or epigenetic changes in mother that could impair placenta function which in turn could lead to cardiovascular or neurological disruption …”
Section: What Are the Potential Mechanisms Underlying The Effects Of mentioning
confidence: 99%
See 1 more Smart Citation
“…These include impaired renal blood flow and an increased incidence of renal disease (183,184), exacerbation of metabolic syndrome/diabetes (185188), changes to the placental circulation (189191) and epigenetic alterations that may affect the cardiorespiratory health of offspring (192,193). …”
Section: Role Of Oxidative Stress In the Cardiovascular Effects Of Aimentioning
confidence: 99%
“…Although the data are limited, some studies have suggested associations between diminished vascularization indices in the placenta during the first trimester of pregnancy and air pollutants, particularly NO2 (Hettfleisch et al 2017). These indices have been shown to be lower in patients with preeclampsia compared with normotensive pregnancies (Costa et al 2010).…”
Section: Potential Mechanismsmentioning
confidence: 99%